Phraseologie kontrastiv und didaktisch: neue Ansätze in der Fremdsprachenvermittlung - Jesenšek, Vida; Fabčič, Melanija Larisa (University of Maribor Press, 2007)
Phraseology Contrastive and Didactic: new approaches in language teaching. No abstract.